2012
DOI: 10.1155/2012/702857
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cell Growth and Induction of Apoptosis byAntrodia camphoratain HER-2/neu-Overexpressing Breast Cancer Cells through the Induction of ROS, Depletion of HER-2/neu, and Disruption of the PI3K/Akt Signaling Pathway

Abstract: Previously, we demonstrated that a submerged fermentation culture of Antrodia camphorata (AC) promotes cell-cycle arrest and apoptosis in human estrogen receptor-positive/negative breast cancer cells. However, whether AC is effective against HER-2/neu-overexpressing breast cancers has not been thoroughly elucidated. In the present study, we showed that AC exhibited a significant cytotoxic effect against HER-2/neu-overexpressing MDA-MB-453 and BT-474 cells. Immunoblot analysis demonstrated that HER-2/neu and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 49 publications
(76 reference statements)
3
36
0
Order By: Relevance
“…CoQ0 may induce the opening of mitochondrial permeability transition pore (PTP) and the production of H 2 O 2 as previously described [32, 33]. Similar to our findings, ROS was also shown to mediate apoptosis of HER-2/neu-overexpressing breast cancer cells induced by the culture broth of A. cinnamomea [34]. We found that CoQ0 exerts a higher cytotoxicity in A549 cancer cells (IC 50 ≈ 15  μ g/mL) than in normal human fibroblast Detroit 551 cells (IC 50 ≈ 42  μ g/mL, data not shown).…”
Section: Discussionsupporting
confidence: 89%
“…CoQ0 may induce the opening of mitochondrial permeability transition pore (PTP) and the production of H 2 O 2 as previously described [32, 33]. Similar to our findings, ROS was also shown to mediate apoptosis of HER-2/neu-overexpressing breast cancer cells induced by the culture broth of A. cinnamomea [34]. We found that CoQ0 exerts a higher cytotoxicity in A549 cancer cells (IC 50 ≈ 15  μ g/mL) than in normal human fibroblast Detroit 551 cells (IC 50 ≈ 42  μ g/mL, data not shown).…”
Section: Discussionsupporting
confidence: 89%
“…Apoptotic resistance in HER-2/neu-overexpressing breast cancer cells is mediated by a loss of FOXO3a activity (25) and we demonstrated that this pathway is inhibited by NOC. Upstream, NOC activates FOXO3a by targeting the Akt pathway.…”
Section: Discussionmentioning
confidence: 86%
“…HT-29 cells pretreated with AC539 showed an increase in IL-1 β expression after radiation treatment, whereas expression of iNOS and TNF-α were decreased after 24-h AC539 pretreatment, and their expression increased in a dose-dependent manner after 48-h AC539 pretreatment ( Figure 5A). Th is eff ect was more obvious in the radiosensitive BT-474 cells ( Figure 5B), apoptosis induction (Lee et al 2012). In radiation therapy, tumor hypoxia is a common cause for treatment failure.…”
Section: Protein Cellmentioning
confidence: 95%